**Propositional Logic MCQs** are very important test and often asked by various testing services and competitive exams around the world. Here you will find all the Important **Propositional Logic MCQs** for Preparation.

The student can clear their concepts for **Propositional Logic**** **online quiz by attempting it. Doing MCQs based **Propositional Logic**** **will help you to check your understanding and identify areas of improvement.

**Propositional Logic Online MCQs with Answers**

In propositional logic, a statement is:

a) A combination of variables and constants.

b) An expression that can be evaluated to true or false.

c) A mathematical equation.

d) An argument with premises and a conclusion.

Which symbol represents the logical OR in propositional logic?

a) ∧

b) ∨

c) ⊕

d) ¬

Which symbol represents the logical AND in propositional logic?

a) ∧

b) ∨

c) ⊕

d) ¬

Which symbol represents the logical NOT in propositional logic?

a) ∧

b) ∨

c) ⊕

d) ¬

Which symbol represents the exclusive OR (XOR) in propositional logic?

a) ∧

b) ∨

c) ⊕

d) ¬

The statement “P ∧ Q” is true when:

a) P is true and Q is false.

b) P is false and Q is true.

c) Both P and Q are true.

d) Both P and Q are false.

The statement “P ∨ Q” is true when:

a) P is true and Q is false.

b) P is false and Q is true.

c) Either P or Q is true.

d) Both P and Q are false.

The statement “P → Q” is true when:

a) P is true and Q is false.

b) P is false and Q is true.

c) Either P or Q is true.

d) Both P and Q are false.

The statement “P ↔ Q” is true when:

a) P is true and Q is false.

b) P is false and Q is true.

c) Either P or Q is true.

d) Both P and Q have the same truth value.

The negation of the statement “P” is represented as:

a) P

b) ¬P

c) P ∧ Q

d) P ∨ Q

The statement “P ∧ Q → R” is equivalent to:

a) (P ∧ Q) → R

b) P ∧ (Q → R)

c) P → (Q ∧ R)

d) (P → Q) ∧ R

The statement “P ∨ (Q ∧ R)” is equivalent to:

a) (P ∨ Q) ∧ R

b) P ∨ (Q ∨ R)

c) (P ∧ Q) ∨ R

d) P ∧ (Q ∨ R)

The statement “¬(P ∧ Q)” is equivalent to:

a) ¬P ∧ ¬Q

b) ¬P ∨ ¬Q

c) ¬P → ¬Q

d) P ∨ Q

The statement “P → (Q ∨ R)” is equivalent to:

a) (P → Q) ∧ R

b) P ∨ (Q → R)

c) ¬P → (Q ∨ R)

d) (P → Q) ∨ (P → R)

The statement “P ∧ (Q ∨ R)” is equivalent to:

a) (P ∧ Q) ∨ R

b) P ∨ (Q ∧ R)

c) (P ∨ Q) ∧ R

d) P ∧ (Q → R)

The statement “P → (Q ∧ R)” is equivalent to:

a) (P → Q) ∧ (P → R)

b) P ∨ (Q ∧ R)

c) ¬P → (Q ∧ R)

d) (P → Q) ∨ R

The statement “P ∧ (Q → R)” is equivalent to:

a) (P ∧ Q) → R

b) P → (Q ∧ R)

c) (P → Q) ∧ (P → R)

d) (P ∨ Q) ∧ R

The statement “P ∨ (Q → R)” is equivalent to:

a) (P ∨ Q) → R

b) P → (Q ∨ R)

c) ¬P → (Q → R)

d) (P → Q) ∨ R

The statement “P ↔ (Q ∧ R)” is equivalent to:

a) (P ↔ Q) ∧ R

b) P ↔ (Q ↔ R)

c) (P ↔ Q) ↔ R

d) P ↔ (Q ∨ R)

The statement “P → (Q ↔ R)” is equivalent to:

a) (P ↔ Q) ↔ R

b) P → (Q ↔ R)

c) (P → Q) ↔ R

d) (P ↔ Q) → R

The statement “P ∧ (Q ↔ R)” is equivalent to:

a) (P ∧ Q) ↔ R

b) P ↔ (Q ∧ R)

c) (P ↔ Q) ∧ R

d) P ∧ (Q → R)

The statement “P ↔ (Q → R)” is equivalent to:

a) (P ↔ Q) ∧ (P ↔ R)

b) P ↔ (Q → R)

c) (P → Q) ↔ (P → R)

d) (P ↔ Q) ∨ (P ↔ R)

The statement “P → (Q ∨ ¬R)” is equivalent to:

a) P ∨ (Q ∧ ¬R)

b) (P → Q) ∨ ¬R

c) ¬P → (Q ∨ ¬R)

d) (P → Q) ∧ ¬R

The statement “P ∨ (Q ∧ ¬R)” is equivalent to:

a) (P ∨ Q) ∧ ¬R

b) P ∨ (Q ∨ ¬R)

c) (P ∧ Q) ∨ ¬R

d) P ∧ (Q ∨ ¬R)

The statement “¬(P ∧ Q) ∨ R” is equivalent to:

a) ¬P ∨ ¬Q ∨ R

b) ¬(P ∨ Q) ∨ R

c) ¬(P ∨ Q ∨ R)

d) ¬P ∧ ¬Q ∨ R